Effects of nitrogen and tiller type on grain yield and physiological responses in rice. Issue 2 (30th March 2017) - Wang, Yang; Lu, Jianwei; Ren, Tao; Hussain, Saddam; Guo, Chen; Wang, Sen; Cong, Rihuan; Li, Xiaokun
Abstract : Tillering is an important agronomic trait for rice population quality and grain production. Nitrogen fertilizer application increased the number of rice tillers, but not every tiller contributes equally to the overall yield. Heterogeneity in tiller yield of rice increased with increasing nitrogen levels. Typically, late emerging tillers contributed less to the grain yield. Under high nitrogen conditions, most of the nutrients were retained in the straw of late emerging tillers; these tillers have high transport efficiency in vascular bundles, but there is less time for nutrients to transport into the grain. Despite the high light intensity, less than half of the light is used for photosynthesis in late emerging tillers. The low activity of enzymes related to grain filling in late emerging tillers is another reason for low yield. Abstract: The increasing food demands from an expanding population necessitate global efforts to increase crop production and ensure food security. The rate of nitrogen (N) fertilizer application is strongly related to crop yield. However, although the application of N fertilizer significantly increases the number of tillers in rice, late emerging tillers usually produce lower yields compared with early emerging tillers. Understanding the physiological constraints of late emerging rice tillers is critical for further increasing rice grain yields. Two-year field experiments, consisting of four nitrogen fertilizer levels, were conducted in order to study variations in the physiological characteristics of different types of tillers. The results revealed that the contributions of late emerging tillers to population rice grain yields improved with increased N levels. However, spikelets per panicle and the grain filling of late emerging tillers were significantly lower than that of the main stems or early emerging tillers under all N levels. The nitrogen harvest index of late emerging tillers was lower than that of main stems and early emerging tillers, and differences gradually increased under higher N rates. Nutrient source deficiency was a primary factor for the low productivity of late emerging tillers. Additionally, rapid malondialdehyde accumulation and delayed emergence determined the short growth duration of late emerging tillers. Further, low actual photochemistry efficacy (ΦPSII ) resulted in insufficient photosynthetic assimilate supply in late emerging tillers, whereas highly constitutive non-photochemical energy dissipation (ΦNO ) might damage the photosynthetic system. Moreover, the low activity of SuSase and spikelets per panicle revealed both inadequate sink activities and storage sites. The identification of these limiting factors in late emerging rice tillers will assist in closing the 'yield gap' between late emerging tillers and early emerging tillers, and contribute to further increasing rice grain yields.